2010
DOI: 10.1086/648676
|View full text |Cite|
|
Sign up to set email alerts
|

Dental Procedures as Risk Factors for Prosthetic Hip or Knee Infection: A Hospital‐Based Prospective Case‐Control Study

Abstract: Dental procedures were not risk factors for subsequent total hip or knee infection. The use of antibiotic prophylaxis prior to dental procedures did not decrease the risk of subsequent total hip or knee infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
156
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(176 citation statements)
references
References 47 publications
4
156
1
10
Order By: Relevance
“…Obesity has been associated with an increased risk of infection in many (9,(17)(18)(19)(20)(21)(22)(23)(24)(25) but not all (26) studies. A body mass index (BMI) threshold of 35 is most commonly used.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity has been associated with an increased risk of infection in many (9,(17)(18)(19)(20)(21)(22)(23)(24)(25) but not all (26) studies. A body mass index (BMI) threshold of 35 is most commonly used.…”
Section: Risk Factorsmentioning
confidence: 99%
“…This may be due to increased biofilm formation in the presence of elevated levels of glucose, as seen in in vitro models (31); impaired leukocyte function; or microvascular changes in patients with diabetes, which may influence wound healing and the development of superficial surgical site infections. However, not all studies have demonstrated a clear link between diabetes and PJI (17,26), and some studies that have shown an increased risk grouped diabetes mellitus with other immunocompromising conditions (24).…”
Section: Risk Factorsmentioning
confidence: 99%
“…[11][12][13] Current evidence suggests that dental procedures play a minor role in the development of infective endocarditis and periprosthetic joint infection. [14][15][16][17][18][19] Increased awareness of antibiotic resistance has also questioned the appropriateness and scope of antibiotic prophylaxis use in dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…26 This statement issued by the ADA has since been supported by numerous studies that have questioned the use of prophylactic antibiotics in patients with prosthetic joints. A large case-control study by Berbari et al 22 showed that antibiotic prophylaxis before dental procedures was not associated with a decreased risk of prosthetic joint infections and suggested that the 2009 guidelines should be reconsidered. Studies by Matar et al 28 and Skaar et al 29 came to similar conclusions.…”
Section: Dental Proceduresmentioning
confidence: 99%